Battery Charging Boost Converter Metode Constant Current-Constant Voltage Mesin Penggiling Kedelai - Irianto; Ahmad Firyal Adila; Muhammad Alvin Nasrullah; Sutedjo; Renny Rakhmawati; Diah Septi Yanaratri (Elposys: Jurnal Sistem Kelistrikan, 2026)
The increasing utilization of renewable energy, such as solar panels, drives the need for efficient and safe energy storage systems. One of the main challenges is achieving a stable battery charging process. The Constant Current–Constant Voltage (CC–CV) method is an effective solution because it maintains a constant current during the initial charging stage and keeps the voltage stable as it approaches full capacity.This study implements a charging system for a 24V 26Ah VRLA battery using a boost converter with PI control based on the CC–CV method. The system operates offline (cycle use), meaning the load is not connected during charging. The constant current stage is carried out at 3.75 A until the voltage reaches 28.8 V, after which the system switches to constant voltage mode with a fixed voltage of 28.8 V and a gradually decreasing current.PI control is applied to maintain system stability and prevent overcurrent and overvoltage. Testing shows that the system is capable of charging the battery from 60% State of Charge (SoC) to full capacity in 2 hours and 30 minutes with an efficiency of 82%–85%. The converter output voltage remains stable at 28.8 V, and the charging current adjusts according to the battery condition.After charging, the battery can be used to supply a soybean grinding machine for 20 minutes. The system is also equipped with a SoC monitoring feature to prevent overdischarge and extend battery life.